Kedudukan Indonesia Dalam Menyikapi Penyelesian Sengketa Internasional Di Laut Cina Selatan - Antonia Immaculata Putri Seran; Bernadus Febriyanto; Yohanes Arman; Pregrinus Rangga (Pusat Riset dan Inovasi Nasional, 2023)
The conflict that occurred in the South China Sea (LCS) becameflash point in the Asia Pacific region. Disputes in the South China Sea involve not only 6 or even 10 countries, but also involve other major powers such as the United States. The six (6) countries referred to are China, Taiwan, Vietnam, the Philippines, Brunei Darussalam, Malaysia, and (4) four other countries namely Cambodia, Singapore, Thailand and including Indonesia. In its development, the South China Sea (LCS) conflict has also started to